Development of emergent ferroelectric nematic liquid crystals with highly fluorinated and rigid mesogens. Issue 19 (4th May 2022) - Song, Yaohao; Li, Jinxing; Xia, Runli; Xu, Hao; Zhang, Xinxin; Lei, Huanyu; Peng, Weifeng; Dai, Shuqi; Aya, Satoshi; Huang, Mingjun
Abstract : A type of highly fluorinated and rigid mesogen distinct from previous aromatic ester-based molecules is designed and validated to exhibit the ferroelectric nematic liquid crystal phase. Abstract : The emerging ferroelectric nematic liquid crystals have been attracting broader interests in new liquid crystal physics and their unique material properties. One big challenge for the ferroelectric nematic research is to enrich the material choice, which is now limited to RM734 and DIO families as representatives, in sharp contrast to the enormously diverse variety of the traditional apolar nematic liquid crystals. Here, we report a design of novel ferroelectric nematic materials with highly fluorinated and rigid mesogens. Noteworthily, they show distinct chemical structural features compared with previous aromatic ester-based molecules. The ferroelectric nematic phase was identified and confirmed through rigorous experiments. The bulk polarization was found to become purely along the long axis director, creating giant dielectric anisotropy. This work demonstrates a great potential for expanding ferroelectric nematic material diversity and will accelerate the corresponding application research and technology innovation.